In silico identification of prospective virulence factors associated with candidiasis in Meyerozyma guilliermondii strain SO from genome dataset - Zainudin, Robiatul Azilah; Sabri, Suriana; Salleh, Abu Bakar; Abu, Arpah; Raja Khairuddin, Raja Farhana; Oslan, Siti Nurbaya (SpringerOpen, 2023)
Meyerozyma guilliermondii is a prospective yeast that has extensively contributed to the biotechnology sector. In 2015, M. guilliermondii strain SO which was isolated from spoiled orange has successfully been developed as an inducer-free expression system and attained a significant impact in producing industrially important recombinant proteins. The species possesses high similarity to Candida albicans which may cause candidiasis. The industrial-benefiting M. guilliermondii strain SO has been underexplored for its virulence status. Thus, this study aimed to document the potential virulence factors through the comprehensive in silico analysis of M. guilliermondii strain SO genome. This analysis demonstrated the molecular characterization which could distinguish the pathogenicity status of M. guilliermondii.